Prophetic Communication Ethics and Digital Ta'awun in the #WargaBantuWarga Movement - Helmi, Badrul; Alfazri, Muhammad; Zahara, Rita; Indra, Farhan (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study analyses how the #WargaBantuWarga movement during the 2025 Sumatra floods functioned as a form of digital mass communication while manifesting the value of ta’awun in the online public sphere. This study employs a qualitative approach with a netnographic method to examine the #WargaBantuWarga movement as a practice of digital mass communication in the context of the 2025 Sumatra floods. Data were collected through digital documentation and non-participant observation, then analysed through data reduction, data display, and conclusion drawing, with source triangulation used to strengthen validity. The findings reveal that #WargaBantuWarga developed into a node of digital mass communication connecting the documentation of suffering, the dissemination of aid information, the mobilisation of donations, moral support, and criticism of the slow formal response. Conversations that continued into the post-disaster phase indicate that the hashtag moved beyond functioning as a simple issue marker and became a medium sustaining the visibility of the crisis while encouraging public engagement. Ta’awun was manifested through ta’awun maklumat, maliyah, ma’nawiyah, and amaliyah, all circulating across platforms. The study concludes that digital mass communication in disaster contexts serves not only as an informational channel, but also as a moral space that communicatively shapes solidarity, responsibility, and collective action. This study contributes to the field of communication studies, particularly digital mass communication, disaster communication, and Islamic communication ethics, by showing how online public participation during disasters can manifest ta’awun as an ethical principle embedded in digital solidarity practices.